2013
DOI: 10.1177/0272431613496638
|View full text |Cite
|
Sign up to set email alerts
|

Aggressive Forms and Functions on School Playgrounds

Abstract: Coders used real-time focal-child sampling methods to observe the playground behavior and victimization experiences of 600 third to sixth grade youth. Person-centered analyses yielded three profiles that specified aggressive function (reactive, proactive) and form (direct, indirect), and conformed to social-information-processing functional classifications of proactive, reactive, and pervasive aggressors. Consistent with social information processing models, direct reactors and pervasive aggressors evidenced p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(7 citation statements)
references
References 39 publications
1
6
0
Order By: Relevance
“…Rather, the profiles engage in all three reactions but show a greater propensity to engage in one of them. This is line with recent studies showing that witnesses could be defenders but also probullies at other times (Frey et al, 2014;Huitsing et al, 2014). Thus, the reasons why "prodefense witnesses" sometimes adopt passive behaviors and "antidefense" and "probullying" witnesses sometimes support school bullying victims must be explored further.…”
Section: Five Witness Profiles With Distinct Behavioral-psychological Characteristicssupporting
confidence: 88%
“…Rather, the profiles engage in all three reactions but show a greater propensity to engage in one of them. This is line with recent studies showing that witnesses could be defenders but also probullies at other times (Frey et al, 2014;Huitsing et al, 2014). Thus, the reasons why "prodefense witnesses" sometimes adopt passive behaviors and "antidefense" and "probullying" witnesses sometimes support school bullying victims must be explored further.…”
Section: Five Witness Profiles With Distinct Behavioral-psychological Characteristicssupporting
confidence: 88%
“…This approach addresses between-person questions (e.g., do students who exhibit higher levels of defending behavior compared with their peers experience an increase in defender self-efficacy over time?). Such an approach assumes an absence of time-invariant individual differences, which stands in contrast to empirical findings suggesting that a student's bystander behaviors vary over time (e.g., Frey et al, 2014;Levy & Gumpel, 2018). In this regard, the random intercept cross-lagged panel model (RI-CLPM) constitutes an improved way of studying longitudinal associations as it accounts for time-invariant, trait-like stability by the inclusion of random intercepts (Hamaker et al, 2015).…”
Section: Previous Researchmentioning
confidence: 99%
“…Recent results demonstrated that individuals do perform multiple roles across different situations and contexts. Frey et al (2014) showed that bystanders can be defenders of targets at one time and encourage perpetrators at another depending on particular circumstances including the setting or people involved. Waasdorp and Bradshaw (2018) reported that bystanders could also be bullies or victims depending on the situation.…”
Section: Classification Of Bullying Participationmentioning
confidence: 99%